The state of food and agriculture 2003-04. (Rome FAO, 2004)
Explores the potential for agricultural biotechnology to address the needs of the world's poor and food insecure. Reviews the historical record of agricultural research in promoting economic growth and food security."--P. vii.
Part I. Agricultural biotechnology: meeting the need of the poor? Section A: Framing the debate. Can biotechnology meet the needs of the poor? -- What is agricultural biotechnology? -- From the Green Revolution to the Gene Revolution -- Section B: The evidence so far. Economic impacts of transgenic crops -- Health and environmental impacts of transgenic crops -- Public attitudes to biotechnology -- Section C: Making biotechnology work for the poor. Research and research policy for the poor -- Capacity building for biotechnology in food and agriculture -- Conclusions: meeting the needs of he poor -- Part II. World and regional review: facts and figures -- Part III. Statistical annex.
"Included in this issue is the SOFA 2003-04 CD-ROM, containing time series data for 150 countries, and regions in English, French and Spanish, together with FAOSTAT software for easy access and use"--P. [4] of cover.
Includes bibliographical references (p. 199-204).
System requirements: Windows (95/98/NT/2000); minimum: Pentium PC, 64 MB RAM; recommended: 128 MB RAM or better; browser: Microsoft Internet Explorer 5 or later, Netscape Navigator 4 or later; CD-ROM drive.
Keywords: Agricultural biotechnology; Agriculture -- Economic aspects; Food production; Produce trade; Transgenic plants -- Risk assessment